PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA POKOK KAMAR HOTEL (STUDI PADA HOTEL GREEN EDEN MANADO) - Siby, Shelby Estereniy; Ilat, Ventje; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2018)
The Activity of Based Costing (ABC) Method is a simple calculation to determine the cost of price / services to explain that the activity were the reason one to make rise the cost of the products, and products that consume activity.The hotel can use Activity Based Costing (ABC) System Method to determine hotel room rate because when they use the Activity economic method in detail, the quality of decision can be improve to be better and making more accurate. The purpose of this research is â€œto obtain the accurate information about Activity Based Costingâ€ in counting the cost calculation rooms Hotel Green Eden Manado since from June, July, and August 2017. The method of analysis that I used is â€œDescriptive Analysis Methodâ€, by conducting to interview to the hotel manager and doing the data collection regarding the costs and amounts of fees. Based on the analysis, there are find that Activity Based Costing System for the month of June. Superior room type, Deluxe room and Suite resulted that the cost of price rooms were lower to compared with the cost by hotel management. For July the calculation of the cost Superior room type was higher than the cost of calculated by the management Hotel. And for the type of Deluxe rooms and Suite rooms were lower to compared with the cost by the Hotel. And for the month of August the calculation for Superior, Suite, and Deluxe rooms resulted that the cost were higher than the cost calculation used by The Hotel Management.Keywords : Activity Based Costing,Â The cost of rooms.